The Effect of Seaweed Extract (Gracilaria spp.) Towards the Freshness Quality Changes of Fresh Milkfish (Chanos chanos) During Cold Storage - Putri, Chairunnisa Ramadhani; Subekti, Sri; yuli pujiastuti, dwi (Journal of Marine and Coastal Science, 2023)
Milkfish (Chanos chanos) is a type of fish that has high economic value and good nutrition but very easy to decay. People often use formaldehyde and preservatives synthesis of the other so that the fish is not quickly decay. Natural ingredients containing antibacterial compounds, one of which is Gracilaria spp, can be used as an alternative as a natural preservative. This study aims to determine the influence of seaweed extract (Gracilaria spp.) to change the freshness quality of the fish, milkfish (Chanos chanos) during cold storage. The design in this research is Completely Randomized Design (CRD) with four replications and two factors, the first factor is the concentration of seaweed extract 700, 600, 500 ppm, and control (without soaking). The second factor is the length of storage time for 0, 3, and 6 days. Analysis of data using Analysis of Variance (ANOVA) and continued with the Duncan's Multiple Distance Test to determine differences between treatments. The results showed that the extract of seaweed (Gracilaria spp.) at a concentration of 500 ppm, 600 ppm, and 700 ppm during cold storage significantly effect (p<0.05) to changes in the quality of freshness of the fish, milkfish (Chanos chanos). The best treatment was at a concentration of 700 ppm. Gracilaria spp extract solution with a concentration of 700 ppm can be used as an antibacterial and to maintain the fresh quality of milkfish based on the total number of bacteria, organoleptic tests and pH tests.